CSR Reporting Practices of Polish Energy and Mining Companies - Elżbieta Izabela Szczepankiewicz (Sustainability, 2016)
Corporate Social Responsibility (CSR) reporting receives much attention nowadays. Communication with stakeholders is a part of assumed social responsibility, thus the quality of information disclosed in CSR reports has a significant impact on fulfilment of the responsibility. The authors use content analysis of selected CSR reports to describe and assess patterns and structure of information disclosed in them. CSR reports of Polish companies have similar structures at a very high level of analysis, but a more detailed study reveals much diversity in approaches to the report’s content. Even fairly similar companies may devote significantly different amounts of space to the same issue. The number of similar stakeholders varies irrespectively of the company’s size. Considerable diversity of reporting patterns results from the nature of CSR reporting, because it concerns highly entity-specific issues. Thus, such considerable diversity is not surprising. However, many initiatives and efforts are devoted to greater comparability of reporting, so a greater degree of uniformity can be expected. Similar conclusions may be drawn from integrated reports’ analysis, though a small sample reflects the relative novelty of this trend.